Development of screening strategies for the identification of paramylon-degrading enzymes. (1st June 2019) - Gissibl, Alexander; Care, Andrew; Sun, Angela; Hobba, Graham; Nevalainen, Helena; Sunna, Anwar
Abstract: Enzymatic degradation of the β-1, 3-glucan paramylon could enable the production of bioactive compounds for healthcare and renewable substrates for biofuels. However, few enzymes have been found to degrade paramylon efficiently and their enzymatic mechanisms remain poorly understood. Thus, the aim of this work was to find paramylon-degrading enzymes and ways to facilitate their identification. Towards this end, a Euglena gracilis -derived cDNA expression library was generated and introduced into Escherichia coli . A flow cytometry-based screening assay was developed to identify E. gracilis enzymes that could hydrolyse the fluorogenic substrate fluorescein di-β-d -glucopyranoside in combination with time-saving auto-induction medium. In parallel, four amino acid sequences of potential E. gracilis β-1, 3-glucanases were identified from proteomic data. The open reading frame encoding one of these candidate sequences (light_m.20624) was heterologously expressed in E. coli . Finally, a Congo Red dye plate assay was developed for the screening of enzyme preparations potentially able to degrade paramylon. This assay was validated with enzymes assumed to have paramylon-degrading activity and then used to identify four commercial preparations with previously unknown paramylon degradation ability.